Efficacy of Technologies on Management of Rice Leaf Folder and Yield - Kedarnath,; Ramesha, T. J.; Mallikarjuna, L.; Biradar, Veershety; Rashmi, R.; Chethan, N.; Shenoy, Harish; Ashwini, S. K.; Kumar, J. Thejaswi (International Journal of Economic Plants, 2025)
The present study was conducted during rabi (November, 2020 to March, 2021 and November, 2021 to March, 2022) in Dakshina Kannada district of Coastal Karnataka, India to study the efficacy of newer insecticide molecule on effective management of rice leaf folder. The field experiments were set up in a completely randomised block design with four treatments and five replications. Results from the present study revealed that, foliar application of (T3) indoxacarb 14.5 SC @ 0.5 ml l-1 during 25 days and 40 days after transplantation was found most effective in reducing leaf folder incidence (3.46%) by 70.92 per cent and higher yield (40.90 q ha-1) leading to 19.59% increase over farmers practice (11.89%) and yield (34.20 q ha-1) respectively. The economic analysis of yield performance from the present study revealed that foliar application of indoxacarb 14.5 SC @ 0.5 ml l-1 during 25 and 40 days after transplantation achieved higher net return (`Rs. 56,911 ha-1) with higher benefit cost ration (1:2.46) as compared to farmer practice recorded lowest net return (44,901) with lowest benefit cost ratio (1:1.98). The study recorded a technology gap 9.10 q ha-1, extension gap of 6.70 q ha-1 and a technology index of 18.20% in T3. The present study, highlighted that the recommended practices are both feasible and economically viable over farmer’s practices, offering a superior option for managing rice leaf folder under field condition.